Comparison of human papillomavirus‐based cervical cancer screening strategies in Tanzania among women with and without HIV. Issue 4 (22nd September 2022) - Kahesa, Crispin; Thomsen, Louise T.; Linde, Ditte S.; Mchome, Bariki; Katanga, Johnson; Swai, Patricia; Manongi, Rachel; Kjaerem, Myassa; Iftner, Thomas; Waldstrøm, Marianne; Mwaiselage, Julius; Rasch, Vibeke; et al.
Abstract: Cervical cancer is the most common female cancer in Eastern Africa, and the World Health Organization (WHO) recommends human papillomavirus (HPV)‐based screening as a key element to eliminate the disease. In this cross‐sectional study from Tanzania, we compared nine HPV‐based cervical cancer screening strategies, including HPV testing at standard cut‐off; HPV testing at increased viral load cut‐offs; HPV testing with partial/extended genotyping, and HPV testing with visual inspection with acetic acid (VIA). We pooled data collected during 2008 to 2009 and 2015 to 2017 from 6851 women aged 25 to 65. Cervical cytology samples were HPV tested with Hybrid Capture 2, and HPV positive samples were genotyped with INNO‐LiPA Extra II. Human immunodeficiency virus (HIV) testing and VIA were done according to local standards. We calculated sensitivity, specificity, positive and negative predictive value of screening strategies, with high‐grade cytological lesions as reference, separately for women with and without HIV. HPV testing at standard cut‐off (1.0 relative light units [RLU]) had highest sensitivity (HIV+: 97.8%; HIV−: 91.5%), but moderate specificity (HIV+: 68.1%; HIV−: 85.7%). Increasing the cut‐off for HPV positivity to higher viral loads (5.0/10.0 RLU) increased specificity (HIV+: 74.2%‐76.5%; HIV−: 89.5%‐91.2%), with modest sensitivity reductions (HIV+: 91.3%‐95.7%; HIV−: 83.5%‐87.8%). Limiting test positivity to HPV types 16/18/31/33/35/45/52/58 improved specificity while maintaining high sensitivity (HIV+: 90.2%; HIV−: 81.1%). Triage with VIA and/or partial genotyping for HPV16/18 or HPV16/18/45 had low sensitivities (≤65%). In conclusion, HPV testing alone, or HPV testing with extended genotyping or increased viral load cut‐offs, may improve cervical cancer screening in Sub‐Saharan Africa. Abstract : What's new? WHO recommends screening with human papillomavirus (HPV) testing to prevent cervical cancer. Few studies have compared sensitivity and specificity of different HPV‐based screening/triage strategies in low‐and‐middle‐income countries. In this cross‐sectional study of 6851 Tanzanian women, we compared nine HPV‐based cervical screening strategies in women with or without HIV. We found that HPV testing alone, or HPV testing with extended genotyping or increased viral load cut‐offs, were promising options for cervical cancer screening in low‐income settings.